EFISIENSI TEKNIS DAN EKONOMIS USAHATANI PADI PANDAN WANGI (Kasus di Kecamatan Warung Kondang, Kabupaten Cianjur) - Rossana Podesta; Dwi Rachmina (Forum Agribisnis, 2011)
The development of rice agribusiness in Indonesia has a strategic position from the economic, social and political aspect. The availability of rice with an affordable price is the government concern through increasing production, productivity and quality. The development of aromatic rice of Pandan Wangi varieties has a big propect in filling the premium rice segment. The pandan wangi varieties is an indigenous varieties of Cianjur but is less favorable to farmers. This is caused by pandan wangi farming, using certified or non certified seed, is alocatively and economically inefficient, despite technically efficient. High Input price, especially seed, can not be supported by low output price. The government is needed to guarantee the availability of certified seed with lower price and controlled the price of unhulled rice and pandan wangi rice.